Low temperature magnetic properties of Nd2Ru2O7. (19th March 2018) - Ku, S T; Kumar, D; Lees, M R; Lee, W-T; Aldus, R; Studer, A; Imperia, P; Asai, S; Masuda, T; Chen, S W; Chen, J M; Chang, L J
Abstract: We present magnetic susceptibility, heat capacity, and neutron diffraction measurements of polycrystalline Nd2 Ru2 O7 down to 0.4 K. Three anomalies in the magnetic susceptibility measurements at 146, 21 and 1.8 K are associated with an antiferromagnetic ordering of the Ru 4+ moments, a weak ferromagnetic signal attributed to a canting of the Ru 4+ and Nd 3+ moments, and a long-range-ordering of the Nd 3+ moments, respectively. The long-range order of the Nd 3+ moments was observed in all the measurements, indicating that the ground state of the compound is not a spin glass. The magnetic entropy of R ln2 accumulated up to 5 K, suggests the Nd 3+ has a doublet ground state. Lattice distortions accompany the transitions, as revealed by neutron diffraction measurements, and in agreement with earlier synchrotron x-ray studies. The magnetic moment of the Nd 3+ ion at 0.4 K is estimated to be 1.54(2) µ B and the magnetic structure is all-in all-out as determined by our neutron diffraction measurements.